1998
DOI: 10.1021/jm970635h
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally Defined Retinoic Acid Analogues. 4. Potential New Agents for Acute Promyelocytic and Juvenile Myelomonocytic Leukemias

Abstract: We recently synthesized several conformationally constrained retinoic acid (RA) analogues [8-(2'-cyclohexen-1'-ylidene)-3, 7-dimethyl-2,4,6-octatrienoic acids with different alkyl substituents at 2' (R1) and 3' (R2) positions on the cyclohexene ring] (Muccio et al. J. Med. Chem. 1996, 39, 3625) as cancer chemopreventive agents. UAB8 (R1 = Et; R2 = iPr), which contains sufficient steric bulk at the terminal end of the polyene chain to mimic the trimethylcyclohexenyl ring of RA, displayed biological properties s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 31 publications
0
54
0
1
Order By: Relevance
“…We have demonstrated that 9cUAB30 compared well with Targretin in its capacity to prevent mammary cancer (21)(22)(23)(24)(25). The in vitro studies presented here also show how similar each rexinoid is in blocking ErbB2-oncogenic transformation, consistent with in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have demonstrated that 9cUAB30 compared well with Targretin in its capacity to prevent mammary cancer (21)(22)(23)(24)(25). The in vitro studies presented here also show how similar each rexinoid is in blocking ErbB2-oncogenic transformation, consistent with in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Materials-9cUAB30 was synthesized at the University of Alabama at Birmingham according to previous methods (21,24). Targretin was provided by Dr. Clinton Grubbs at UAB.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the elevation of triglycerides levels by 9-cis-RA, TRG, and various retinoids has been known for many years and is a major concern in the use of these agents, particularly in a cancer-prevention setting (Grubbs et al, 2006;Kolesar et al, 2010). We previously designed selective RXR agonists based on 9-cis-RA that are effective agents with lower toxicity and with varying ability to inhibit mammary cancer formation (Muccio et al, 1998;Atigadda et al, 2003;.Grubbs et al, 2006). One of these analogs (UAB30) did not increase serum triglycerides in rodents (Grubbs et al, 2006) and humans (Kolesar et al, 2010) but was nevertheless effective in preventing mammary cancers in rats.…”
Section: Introductionmentioning
confidence: 99%